Identity dynamics and project - Costalat-Founeau, Anne-Marie (2018)
The aim of this article is to present the processes that drive the phasic identity dynamics of social identity, allowing us to define simultaneously a representation of self and the personal and professional project. As a result, it implies differentiated levels of anchorages in the organizations, groups and society that contribute to shaping the self-project. We will illustrate this, thanks to cases and situations related to the context, autobiographical memory but also emotions, feeling of capacity and motivation. One of our orientations stipulates that social identity is organized in a representational dynamic in which the phases of action become facilitators of identity construction and leaving forms in experiential memory necessary for the construction of the project